Analisis Fitokimia dan Uji Aktivitas Antioksidan Ekstrak Aseton Daun Kelor (Moringa oleifera) - Ashari, Arif; Meilita, Dwi; Ciptati; Kurniawan, Rahmat; Sudarmanto, Irwan; Agung, Ahmad Anggraria Jaya; Abdussalam, Moch (Stannum : Jurnal Sains dan Terapan Kimia, 2025)
Indonesia’s rich biodiversity includes Moringa oleifera, widely used in traditional medicine. However, environmental factors such as climate, soil, and agronomic practices can influence the phytochemical composition and bioactivity of its leaves. This study aimed to investigate the phytochemical profile and antioxidant activity of acetone extracts of M. oleifera leaves sourced from South Lampung. Leaves were air-dried, powdered, and extracted via maceration in acetone. Phytochemical screening employed standard reagents (Dragendorff’s and Mayer’s for alkaloids; Mg and HCl for flavonoids; Liebermann–Burchard for steroids and triterpenoids; FeCl₃ for tannins; foam test with 2 N HCl for saponins). Antioxidant capacity was assessed using the DPPH (2,2-diphenyl-1-picrylhydrazyl) assay. Phytochemical screening revealed the presence of alkaloids, flavonoids, steroids, triterpenoids, and tannins, while saponins were not detected. In the DPPH assay, percentage inhibition increased with concentratio, yielding an IC₅₀ of approximately 209.4 ppm. This relatively high IC₅₀ indicates weak radical-scavenging activity under the present conditions. The findings provide the first detailed report of phytochemical constituents and DPPH-based antioxidant capacity for acetone extracts of M. oleifera leaves from South Lampung. Although secondary metabolites with known bioactivities were detected, the weak DPPH scavenging suggests that acetone may not optimally extract the most potent antioxidant compounds or that local growth conditions yield lower phenolic/flavonoid concentrations.